The impact of improper waste disposal on human health and the environment: a case of Umgungundlovu District in KwaZulu Natal Province, South Africa - Raphela, Tlou; Manqele, Nelisiwe; Erasmus, Mariana (Frontiers in Sustainability, 2024)
Waste generation has increased drastically worldwide in recent decades, with less than 20% of waste recycled each year, and onethird of all food produced wasted. With Sustainable Development Goal 12 advocating for changing how we consume, produce, and dispose of items, the cruciality of driving a more sustainable future lies in how we dispose of our waste. Improper waste disposal has always been a global concern. This study assessed the impacts of improper waste disposal on human health and the environment in the KwaZulu Natal Province of South Africa. The study applied a mixed-method approach to a semi-structured questionnaire.Using Statistical Package for Social Scientists (SPSS) and Microsoft Excel, the study applied a series of Chi-Squared tests of independence, regression, and descriptive statistics to the data. This study shed light on the complex dynamics surrounding the awareness and perception of risks associated with improper waste disposal. While a fair level of knowledge exists concerning the general risks, there are notable gaps in understanding specific human health risks related to improper waste disposal. The statistically insignificant relationships between demographic variables and critical questions regarding risk awareness suggest that demographic factors do not significantly influence awareness. This implies a need for targeted educational campaigns that transcend demographic boundaries to address the identified gaps in knowledge. Furthermore, the findings highlight a critical disparity in awareness regarding specific human health risks associated with improper waste disposal. This underscores the importance of enhancing public education and outreach programs to ensure a comprehensive understanding of the potential dangers to human health. The insignificant relationship between information availability and community concern about health impacts emphasizes the need for improved communication strategies. Efforts should focus on delivering accurate and accessible information to communities, fostering a sense of concern and responsibility regarding the health implications of improper waste disposal. The statistically significant relationship revealed by the regression model on the cost of clean-up for the municipality and waste generation necessitates re-evaluating waste management policies. The study municipality should explore sustainable waste management practices to mitigate the economic burden posed by increased waste generation.